Improved Detection of Circulating Tumor Cells in Metastatic Colorectal Cancer by the Combination of the CellSearch(®) System and the AdnaTest(®) - Gorges, Tobias M. (PLoS One, 2016)
Colorectal cancer (CRC) is one of the major causes of cancer-related death and reliable blood-based prognostic biomarkers are urgently needed. The enumeration and molecular characterization of circulating tumor cells (CTCs) has gained increasing interest in clinical practice. CTC detection by CellSearch(®) has already been correlated to an unfavorable outcome in metastatic CRC. However, the CTC detection rate in mCRC disease is low compared to other tumor entities. Thus, the use of alternative (or supplementary) assays might help to itemize the prognostic use of CTCs as blood-based biomarkers. In this study, blood samples from 47 mCRC patients were screened for CTCs using the FDA-cleared CellSearch(®) technology and / or the AdnaTest(®). 38 samples could be processed in parallel. We demonstrate that a combined analysis of CellSearch(®) and the AdnaTest(®) leads to an improved detection of CTCs in our mCRC patient cohort (positivity rate CellSearch(®) 33%, AdnaTest(®) 30%, combined 50%). While CTCs detected with the CellSearch(®) system were significantly associated with progression-free survival (p = 0.046), a significant correlation regarding overall survival could be only seen when both assays were combined (p = 0.013). These findings could help to establish improved tools to detect CTCs as on-treatment biomarkers for clinical routine in future studies.